Reemployment of Displaced Workers – The Case of a Plant Closing on a Remote Region in Finland - Jolkkonen, Arja; Koistinen, Pertti; Kurvinen, Arja (Nordic Journal of Working Life Studies, 2012)
The aims of this article are to examine the reemployment of displaced workers and individual factors that predict reemployment and education, earnings in new jobs, and paths to reemployment. This article is based on a case study of the closing down of the Perlos Ltd plants in North Karelia in eastern Finland. From the 1990s, the Perlos Corporation grew from a Nokia subcontractor into a globally operating limited company with a global workforce of over 13,000 workers and almost 2,000 workers in North Karelia. In 2007, the corporation closed down all its production activities in Finland. In the case study, various data sources were used but this article is based mainly on the questionnaire conducted in 2008 among 1,217 trade union members. Logistic and multinomial regression analyses are used as analysis methods. Against expectations, the fast reemployment of the displaced workers was a surprise, which can be explained by the good demand and hidden need for labor in other firms in this region. However, the demand was specific and differentiated between the workers’ job opportunities. White-collar workers had better chances of reemployment. Gender, next to the occupational status, was an important predictor for reemployment. On the other hand, education, the willingness to move, and family status were not statistically significant explanatory factors for reemployment. The age of the job seekers was one important factor predicting unemployment.